Destruction of biomass tar model compound in a rotating gliding arc plasma catalytic system: Contribution of typical transition metals in Ni-based bimetallic catalyst. (1st September 2022) - Zhang, Hao; Xu, Ruiyang; J, Ananthanarasimhan; Zheng, Jiageng; Wan, Jieying; Wang, Kaiyi; Lan, Bingru; Yan, Jianhua; Li, Xiaodong
Highlights: A synergy of plasma and Ni-based catalysts was observed in tar destruction process. NiCu and NiCo bimetallic catalysts are superior to Ni catalyst in terms of activity. NiCu catalyst offered a maximum tar conversion of up to 94.3% coupling with plasma. The producer gas can be significantly upgraded by plasma catalytic tar destruction. NiCu and NiCo showed excellent stability in a 24-hour operation test. Abstract: In this work, the destruction of toluene as a biomass tar model compound has been investigated in a rotating gliding arc (RGA) plasma catalytic system focusing on understanding the contribution of typical transition metals (Fe, Co, Cu) in Ni-based bimetallic catalyst. Investigations were conducted to elucidate their synergy with plasma under simulated gasifier gas (SGG) to destruct toluene and their effect on value-added benefits such as the enhanced heat content of the reacted producer gas. Results showed that the N2 environment offered better performance than the SGG environment, especially at high tar concentration, due to a more abundance of N2 excited species. The loading of Ni on the Al2 O3 catalyst remarkably enhanced the tar conversion from 80.7% to 93.1%. Except for the NiFe, the bimetallic catalysts improved conversion and reduced specific energy consumption (SEC). Primarily, the NiCu catalyst provided a maximum tar conversion of up to 94.3% and significantly enhanced the heat content of the producer gas by 29% from that of the SGG. The minimum SEC of 64.5 kWh/kg was achieved by the NiCo, which also showed the best sintering resistance. In the 24-hour plasma-catalytic operation, NiCu and NiCo showed excellent stability with only a slight drop in the tar conversion (∼94% to ∼ 91%) after 10–12 h. Analysis of by-products indicated back spillover of OH and O, which could help clean the metal surface. Thermogravimetric analysis of the spent catalyst indicated that the coke deposited is likely composed of the aromatic compounds of boiling point in the range of 100 °C to 300 °C.